Heterogene Daten in den Digital Humanities: Eine Architektur zur forschungsorientierten Förderation von Kollektionen - Tobias Gradl; Andreas Henrich; Christoph Plutte (Zeitschrift für digitale Geisteswissenschaften, 2015)
Traditional approaches to data integration are typically based on the harmonization of heterogeneous data with respect to the constraints of a globally integrative data structure, such as a global schema or ontology. This paper illustrates the limitations of such a harmonization-based approach in the specific context of the Digital Humanities and shows how a research-oriented and case-based data federation can be facilitated by the DARIAH-DE federation architecture. Based on the collection, schema, and crosswalk registries, collections and the data schemata they utilize can be registered and flexibly associated – resulting in the ability to create broad and comprehensive as well as discipline-specific views of research data.